Determinación del Contenido de Carbono en el Suelo en una Plantación de Melina (gmelina arborea) en la Parroquia Pucayacu del Cantón La Maná, Provincia de Cotopaxi - Cepeda Granja, Renán Alejandro (2019)
Soil is a vulnerable resource against degradation and overexploitation. It has been shown that monocultures can significantly reduce fertility and organic matter content in the soil. However, soils are capable to stor more carbon than the atmosphere and vegetation, which makes imperative to determine its carbon storage capacity. The objective of this pesearch was to determine the carbon content of the soil in a Gmelina arborea plantation, located in the Pucayacu of La Maná Canton. Initially, the study area and sampling points were processed; where the necessary samples were taken for the analysis of the physical characteristics - soil chemical. Seven sampling points were established on the whore surface of the plantation, taking a total of 28 soil samples, a depth of 30.0 cm. The quantification of the organic carbon content in the soil was carried out to determine the percentage of organic matter at the laboratory level, which was collated whit respect to the Van Benmelen factor. Finally, the total organic carbon content of the soil was estimated using the proposed equation by Perman, determining the apparent density, sampling depth and percentage of organic soil carbon. It was determined that the organic carbon storage capacity of the soil is too high, with an average of 58.32 ton / ha. This information allows to conclude that the soil of this plantation is not being affected by the Gmelina arborea cultivation.